Analisis Komunitas Online Wikipedia Bahasa Jawa - Wibowo, Danny (Universitas Semarang, 2022)
The Javanese Wikipedia Community is one of the communities under the auspices of Wikimedia Indonesia. The Community has the purpose of cultivating the Javanese language among Indonesian society. One of their programs includes writing articles but in Javanese language. Due to the Covid-19 pandemic, most of their activities have shifted to online systems. Because of the switching to an online community, researchers want to do some further research on the process and adaptation that occurs. This study will use the Participatory Action Research (PAR) method, which makes the community as an object of research to find problems in the community without changing the values in the community. With the implementation of this research, it is expected to find the value of social change that can be adapted in the Javanese Wikipedia community and other online communities.